Atividade diária de dipsadídeos neotropicais - Torello-Viera, Natália Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Daily activity is an understudied aspect among Neotropical snakes. This region possesses high species richness, and bears an extremely diverse ecology. In this context, the present study sought to provide information on activity patterns of several species of dipsadids, which is the most diverse group of snakes at the neotropical region. A total of 49 individuals were observed, comprising nine species, from different lineages: Atractus pantostictus and Sibynomorphus mikanii, Apostolepis assimilis, Erythrolamprus aesculapii, and Liophis miliaris, Oxyrhopus guibei, Philodryas patagoniensis, and Tomodon dorsatus and Thamnodynastes strigatus. The specimens were housed in captivity for 10 consecutive days and monitored by CCTV system. Most species presented predominantly diurnal activity, except A. pantostictus, S. mikanii and O. guibei. Apostolepis assimilis, L. miliaris and O. guibei showed bimodal activity pattern, as specimens of E. aesculapii individually presented two daily peaks of activity, even so the time of such peaks has differed among the individuals. The analysis of similarity suggests that the pattern of activity is preserved in some groups (E. aesculapii and L. miliaris, tribe Xenodontini, and the Dipsadini A. pantostictus and S. mikanii). Availability of food in the natural environment and climatic factors also seem to influence activity, beyond the reproductive state, and ontogenetic variation

A atividade diária é um aspecto pouco estudado entre as serpentes neotropicais. Essa região abriga grande riqueza de espécies com ecologia extremamente diversificada. Nesse contexto, este estudo buscou fornecer informações sobre padrões de atividade de várias espécies de dipsadídeos, o grupo de serpente mais diversificado da região neotropical. Foram observados 49 indivíduos de nove espécies, pertencentes a diferentes linhagens: Atractus pantostictus, Sibynomorphus mikanii, Apostolepis assimilis, Erythrolamprus aesculapii, Liophis miliaris, Oxyrhopus guibei, Philodryas patagoniensis, Thamnodynastes strigatus e Tomodon dorsatus. Os espécimes foram mantidos em cativeiro e monitorados por dez dias consecutivos por sistema de circuito interno. As espécies apresentaram atividade predominantemente diurna, com exceção de A. pantostictus, S. mikanii e O. guibei. Apostolepis assimilis, L. miliaris e O. guibei apresentaram padrão de atividade bimodal, além de E. aesculapii, que individualmente apresentou dois picos de atividade diários, embora o horário de tais picos tenha diferido entre os indivíduos. A análise de similaridade sugere que o padrão de atividade seja conservado em alguns grupos (E. aesculapii e L. miliaris, da tribo Xenodontini, e os dipsadíneos A. pantostictus e S. mikanii). Disponibilidade de alimento no ambiente natural e fatores climáticos também parecem influenciar a atividade, além do estado reprodutivo e variação ontogenética
Keywords: Ecologia animal; Cobra; Animais - Comportamento; Conservação biológica; História natural; Snakes